2018
DOI: 10.1371/journal.pntd.0006815
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic activation of the vitamin D antimicrobial pathway by M. leprae infection is inhibited by type I IFN

Abstract: Following infection, virulent mycobacteria persist and grow within the macrophage, suggesting that the intrinsic activation of an innate antimicrobial response is subverted by the intracellular pathogen. For Mycobacterium leprae, the intracellular bacterium that causes leprosy, the addition of exogenous innate or adaptive immune ligands to the infected monocytes/macrophages was required to detect a vitamin D-dependent antimicrobial activity. We investigated whether there is an intrinsic immune response to M. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…4d ). These results indicate that 1,25D produced by macrophages following engagement of TLR1/2 26 , is able to act in an autocrine or intracrine manner to enhance CRIg expression.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…4d ). These results indicate that 1,25D produced by macrophages following engagement of TLR1/2 26 , is able to act in an autocrine or intracrine manner to enhance CRIg expression.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…4a ). The TLR1/2 agonist Pam3CSK4, is known to increase the expression of CYP27B1 in macrophages 26 . Using a combination of 25D and Pam3CSK4, we investigated whether treatment with these agents for 24 h causes an increase in CRIg expression.…”
Section: Resultsmentioning
confidence: 99%
“…This response is intrinsically activated in M leprae-infected macrophages but blocked through the induction of type I IFN by M leprae. 105 The production of IFNβ and OAS1 in infected monocytes/macrophages in vitro inhibited CYP27B1, which converts inactive prohormone substrate 25-hydroxyvitamin D (25D) to active vitamin D hormone 1α,25-dihydroxyvitamin D required for the antimicrobial response. In conjunction with these in vitro studies, in lesions of lepromatous patients high expression of type I interferon genes and a low expression of CYP27B1 were observed.…”
Section: Vitamin D Not So Healthy For M Lepraementioning
confidence: 99%
“…The vitamin D–dependent pathway is essential for the bacterial killing in M1 macrophages. This response is intrinsically activated in M leprae –infected macrophages but blocked through the induction of type I IFN by M leprae 105 . The production of IFN‐β and OAS1 in infected monocytes/macrophages in vitro inhibited CYP27B1, which converts inactive prohormone substrate 25‐hydroxyvitamin D (25D) to active vitamin D hormone 1α,25‐dihydroxyvitamin D required for the antimicrobial response.…”
Section: Macrophages: Key Determinants Of the Innate Response To M Lementioning
confidence: 99%
“…Macrophages in the Pathogenesis of Leprosy DOI: http://dx.doi.org/10.5772/intechopen.88754 D-mediated antimicrobial pathway via the induction of type I IFN [40]. Although previous studies have demonstrated the activation of antimicrobial pathways in IL-15-differentiated macrophages, there is no study demonstrating how vitamin D status modulates IL-15-differentiated macrophage phenotype and function.…”
Section: Introductionmentioning
confidence: 99%